ANALYSIS OF REINFORCED SOIL SLOPE WITH MSE (MECHANICALLY STABILIZED EARTH) SYSTEM - Mufti, Yanda
Slope stability analysis involves evaluating the stability condition and performance of a slope. Conducting a slope stability study in the research area is necessary to determine the safety factor (FoS) value of the slope when using the Mechanically Stabilised Earth (MSE) reinforcement system. Mechanically stabilized earth walls (MSE) are typically employed to provide structural support for embankments or earthworks in infrastructure projects such as mines, bridges, and highways. This study was conducted at the filtration plant project on the Martabe site. The walls were constructed using a layering technique, with alternating layers of soil and reinforcement applied from the base upwards. Analysis of the stability of reinforced walls or reinforced slopes using Mechanically Stabilized Earth (MSE) conceptually has a safety factor calculation. This is expressed as FoS = {(Resisting Force + Reinforcement Loads)/(Driving Force)}. Determining the safety factor value for embankment slopes through the MSE system involves empirical analysis using the numerical methods of the Finite Element Method (FEM) and the Limit Equilibrium Method (LEM). Input parameters include material properties, soil properties, and reinforcement properties that were obtained from UCS test findings in the laboratory and from the reports on geotechnical investigations in the research area. The FoS value found from bishop’s method was 2.3 and the Janbu method 2.1 in the data analysis of this study. The MSE wall is deemed stable at a critical SRF value of 2.4 with a displacement of 154 mm from numerical modeling and 160 mm from field measurements horizontally.